2024
DOI: 10.1038/s41598-024-52888-6
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane stem factor nanodiscs enhanced revascularization in a hind limb ischemia model in diabetic, hyperlipidemic rabbits

Eri Takematsu,
Miles Massidda,
Gretchen Howe
et al.

Abstract: Therapies to revascularize ischemic tissue have long been a goal for the treatment of vascular disease and other disorders. Therapies using stem cell factor (SCF), also known as a c-Kit ligand, had great promise for treating ischemia for myocardial infarct and stroke, however clinical development for SCF was stopped due to toxic side effects including mast cell activation in patients. We recently developed a novel therapy using a transmembrane form of SCF (tmSCF) delivered in lipid nanodiscs. In previous studi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Interestingly, however, the positive effects of SCF on osteogenesis, possibly through the c-Kit-Akt signaling pathway, have been recognized in recent years, which may also suggest that SCF may have beneficial effects on osteonecrosis repair ( 64 , 65 ). Additionally, studies have shown that SCF can stimulate cell migration and proliferation, promote blood vessel formation and maturation, and play an important role in angiogenesis and tissue engineering, which may be a potential therapeutic target for osteonecrosis ( 66 , 67 ). While only a limited number of clinical observational studies or meta-analyses have investigated the correlation between SCF and osteonecrosis or drug-induced osteonecrosis, our current MR analysis presents compelling evidence suggesting that elevated levels of circulating SCF are indeed associated with an increased risk of osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, however, the positive effects of SCF on osteogenesis, possibly through the c-Kit-Akt signaling pathway, have been recognized in recent years, which may also suggest that SCF may have beneficial effects on osteonecrosis repair ( 64 , 65 ). Additionally, studies have shown that SCF can stimulate cell migration and proliferation, promote blood vessel formation and maturation, and play an important role in angiogenesis and tissue engineering, which may be a potential therapeutic target for osteonecrosis ( 66 , 67 ). While only a limited number of clinical observational studies or meta-analyses have investigated the correlation between SCF and osteonecrosis or drug-induced osteonecrosis, our current MR analysis presents compelling evidence suggesting that elevated levels of circulating SCF are indeed associated with an increased risk of osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%